PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM PADA PASAR MODAL SYARIAH - Windy Sri Wahyuni (Universitas Medan Area, 2015)
Shareholders in the Islamic capital market find it difficult to monitor whethersharia principles have been implemented by the company issuing the shares of sharia.Supervision of the company that has issued shares of sharia has become crucial to ensurethat the term sharia is not just a mere label, but it must animate every activity of thecompany. In October 2004 Bapepam has officially formed a special unit Echelon IV levelwhich oversees the development of the Islamic capital market policy in the Indonesiancapital market. The formation of a special unit is expected to be born Islamic capitalmarket legal basis as legal protection for shareholders in the Islamic capital market inIndonesia